Comparing Efficiency of American Fisheries Society Standard Snorkeling Techniques to Environmental DNA Sampling Techniques. (4th May 2017) - Ulibarri, Roy M.; Bonar, Scott A.; Rees, Chris; Amberg, Jon; Ladell, Bridget; Jackson, Craig
Abstract: Analysis of environmental DNA (eDNA) is an emerging technique used to detect aquatic species through water sampling and the extraction of biological material for amplification. Our study compared the efficacy of eDNA methodology to American Fisheries Society (AFS) standard snorkeling surveys with regard to detecting the presence of rare fish species. Knowing which method is more efficient at detecting target species will help managers to determine the best way to sample when both traditional sampling methods and eDNA sampling are available. Our study site included three Navajo Nation streams that contained Navajo Nation Genetic Subunit Bluehead Suckers Catostomus discobolus and Zuni Bluehead Suckers C. discobolus yarrowi . We first divided the entire wetted area of streams into consecutive 100‐m reaches and then systematically selected 10 reaches/stream for snorkel and eDNA surveys. Surface water samples were taken in 10‐m sections within each 100‐m reach, while fish presence was noted via snorkeling in each 10‐m section. Quantitative PCR was run on each individual water sample in quadruplicate to test for the presence or absence of the target species. With eDNA sampling techniques, we were able to positively detect both species in two out of the three streams. Snorkeling resulted in positive detection of both species in all three streams. In streams where the target species were detected with eDNA sampling, snorkeling detected fish at 11–29 sites/stream, whereas eDNA detected fish at 3–12 sites/stream. Our results suggest that AFS standard snorkeling is more effective than eDNA for detecting target fish species. To improve our eDNA procedures, the amount of water collected and tested should be increased. Additionally, filtering water on‐site may improve eDNA techniques for detecting fish. Future research should focus on standardization of eDNA sampling to provide a widely operational sampling tool. Received July 27, 2016; accepted March 8, 2017 Published online May 4, 2017